Potential of Renewable Energy in North Sumatra Until 2028 Using LEAP - Muhammad Irwanto; David Prandi Purba; Indra Nisja (ETAPs (Journal Electronics, Telecommunication, Electrical, and Physics Science, 2021)
Energy is needed to support human activities so far. The need for energy from year to year continues to increase. The current use of energy only comes from fossil energy such as coal and oil. This fossil energy reserve will decrease every year. To overcome this problem, a potential alternative energy source that can replace fossil energy is needed, namely new and renewable energy. The potential for new and renewable energy is one of the alternative sources of energy supply and security in North Sumatra Province. To ensure the resilience of new and renewable energy to run in a sustainable manner, it is necessary to analyze the potential of new and renewable energy in North Sumatra until 2028 using LEAP software. The results obtained are the potential for new and renewable energy in North Sumatra in 2028 which has great potential, namely water energy, wind energy and biomass energy. Hydro energy has a potential growth of 3.7 million megawatt-hours in 2028. Meanwhile, wind energy has a potential growth of 2.6 million megawatt-hours and biomass energy has a potential growth of 27.0 million megawatt-hours in 2028.